(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Blood veins clinical diagnosis good developed despite , it damage level and forecast to determine such as important problems solution does not That’s it due to the diagnosis of stroke , first next , hemorrhagic and ischemic of a stroke differential diagnostics , as well as other diseases ( first in line voluminous processes ) with differential diagnosis to do necessary​